2022
DOI: 10.1021/acs.jnatprod.2c00101
|View full text |Cite
|
Sign up to set email alerts
|

Silencing Tautomerization to Isolate Unstable Physalins fromPhysalis minima

Abstract: The inherent structural instability of some physalins has hampered the isolation and identification of these compounds for approximately 50 years, and an effective method to overcome these challenges remains unavailable. In the present study, the unprecedented tautomerization mechanism of unstable physalins was elucidated by performing isotopic labeling experiments and DFT calculations, which led to the successful separation of tautomers and isolation of highly pure products for the first time. As a result, 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Their structures were established by various spectroscopic data and quantum chemical calculations. Twenty-three known withanolide derivatives ( 4 – 26 ), withaminimin ( 4 ), withagulatin A ( 5 ), physagulin A ( 6 ), physagulin B ( 7 ), physagulin J ( 8 ), physapubenolide ( 9 ), physagulide J ( 10 ), (20 S , 22 R )-15α-acetoxy-5α-chloro-6β,14β-dihydroxy-1-oxowitha-2,24-dienolide ( 11 ), physagulin F ( 12 ), physalin H ( 13 ), physalin B ( 14 ), isophysalin B ( 15 ), physalin D ( 16 ), physalin G ( 17 ), physalin E ( 18 ), physalin I ( 19 ), physalin F ( 20 ), 25-OH-physalin D ( 21 ), physaminin M ( 22 ), physaminin K ( 23 ), 5α,6β-dihydroxyphysalin R ( 24 ), aromaphysalin A ( 25 ), and aromaphysalin B ( 26 ), were assigned by comparing their NMR data with those in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Their structures were established by various spectroscopic data and quantum chemical calculations. Twenty-three known withanolide derivatives ( 4 – 26 ), withaminimin ( 4 ), withagulatin A ( 5 ), physagulin A ( 6 ), physagulin B ( 7 ), physagulin J ( 8 ), physapubenolide ( 9 ), physagulide J ( 10 ), (20 S , 22 R )-15α-acetoxy-5α-chloro-6β,14β-dihydroxy-1-oxowitha-2,24-dienolide ( 11 ), physagulin F ( 12 ), physalin H ( 13 ), physalin B ( 14 ), isophysalin B ( 15 ), physalin D ( 16 ), physalin G ( 17 ), physalin E ( 18 ), physalin I ( 19 ), physalin F ( 20 ), 25-OH-physalin D ( 21 ), physaminin M ( 22 ), physaminin K ( 23 ), 5α,6β-dihydroxyphysalin R ( 24 ), aromaphysalin A ( 25 ), and aromaphysalin B ( 26 ), were assigned by comparing their NMR data with those in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Early in 2002, researchers reported that physalin A in 50% methanol solution underwent tautomerization and generated physalin N [ 22 ]. Recently, the mechanism of physalin’s tautomerization was detailed, revealed by Zou’s group [ 23 ]. It was reported that H 2 O was the key factor leading to the instability of physalins and even a small amount of H 2 O (0.5%) in solution triggered interconversion [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the mechanism of physalin’s tautomerization was detailed, revealed by Zou’s group [ 23 ]. It was reported that H 2 O was the key factor leading to the instability of physalins and even a small amount of H 2 O (0.5%) in solution triggered interconversion [ 23 ]. Based on these reports, there is no doubt that physalin A is unstable in whole blood or plasma, which contains a large amount of H 2 O.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing lactone-type cytosporones 1&2, (±)-3 and 4, (±)-3 showed promising antimicrobial activities, which would be significantly weakened with either the aliphatic side chain oxygenated (1&2) or the 7-OH deficiency (4). As for phenyl-type cytosporones 5, 6, 7, and 8, 6 showed better antimicrobial activities, which would also be attenuated with the octanoyl oxygenated (5), shortened to be a hexanoyl (8), or the acetylethoxyl replaced by an acetylmethoxyl (7).…”
Section: Epimerization Mechanismmentioning
confidence: 99%
“…Tautomeric and stereoisomerized compounds are common in the field of natural products research, especially for ketone–enol, enamine–imino, hemiketal–aldol, , and (retro-)­oxa-Micheal addition tautomerism. Convincing hypotheses were proposed to clarify the converting mechanism, and NMR calculation, acid or alkali treatment, chiral-phase high-performance liquid chromatography (HPLC) analysis, and methylation reactions were reported to verify some of those hypotheses. …”
Section: Introductionmentioning
confidence: 99%